Bortezomib plus EPOCH is effective as frontline treatment in patients with plasmablastic lymphoma - Castillo, Jorge J. (2019)
Plasmablastic lymphoma (PBL) is a rare and aggressive CD20‐negative lymphoma associated with poor outcomes. Multiple studies have shown median survival times of 12–18 months (Castillo et al, 2012; Schommers et al, 2013; Morscio et al, 2014). Several case reports and small case series have suggested an increased response rate in patients treated with bortezomib alone or in combination, especially the combination of bortezomib and dose‐adjusted etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin (V‐EPOCH) (Castillo et al, 2015a; Fedele et al, 2016). Due to its rarity, prospective studies exclusively in PBL patients are unlikely to be performed. We evaluated the potential therapeutic value of V‐EPOCH in patients with PBL.